Secondary battery manufacturing method

A two-step electrolyte composition process for secondary batteries addresses issues of leakage, resistance, and electrode tab corrosion by using lithium bis(fluorosulfonyl)imide inside the assembly and forming a gel polymer electrolyte outside, enhancing thermal stability and rigidity while extending battery life.

JP2025501639AActive Publication Date: 2025-01-22LG ENERGY SOLUTION LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024539059
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-14
Filing Date
2023-01-13
Publication Date
2025-01-22
Estimated Expiration
2043-01-13

AI Technical Summary

Technical Problem

Conventional secondary batteries face issues with liquid electrolytes such as leakage, decreased safety, and decreased cell rigidity, while gel polymer electrolytes suffer from higher interfacial resistance and lower ionic conductivity, and lithium salts like lithium bis(fluorosulfonyl)imide cause electrode tab corrosion.

Method used

A two-step electrolyte composition process is employed, where a first electrolyte composition containing lithium bis(fluorosulfonyl)imide is injected and impregnated into the electrode assembly, followed by a second electrolyte composition that forms a gel polymer electrolyte outside the assembly, excluding lithium bis(fluorosulfonyl)imide to reduce resistance, improve thermal stability, and prevent electrode tab corrosion.

Benefits of technology

The method reduces resistance, enhances thermal stability, prevents electrolyte leakage, and improves cell rigidity, thereby extending the long-term life of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501639000001_ABST
    Figure 2025501639000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for producing a secondary battery, the method including the steps of (S1) accommodating an electrode assembly in a battery case, (S2) injecting a first electrolyte composition into the battery case to impregnate the electrode assembly, (S3) injecting a second electrolyte composition into the battery case, and (S4) curing the second electrolyte composition, wherein an electrode tab is connected to the electrode assembly and the electrode tab is extended to the outside of the electrode assembly, the first electrolyte composition includes a 1-1 lithium salt including at least one selected from the group consisting of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and a first solvent, the second electrolyte composition includes an oligomer and a second solvent, and the second electrolyte composition does not include lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0005910 filed on January 14, 2022, and Korean Patent Application No. 10-2022-0006029 filed on January 14, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated as part of this specification.

[0002] The present invention relates to a method for producing a secondary battery. [Background technology]

[0003] 2. Description of the Related Art Along with technological development and increasing demand for electronic devices, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries having high energy density and voltage have been commercialized and are widely used.

[0004] The secondary battery may be manufactured, for example, by housing an electrode assembly in which electrodes and separators are alternately stacked and electrode tabs connected to the electrode assembly in a battery case, injecting an electrolyte into the battery case, and sealing the battery case.

[0005] Conventionally, electrolytes in a liquid state, particularly ion-conductive organic liquid electrolytes in which salts are dissolved in non-aqueous organic solvents, have been mainly used as electrolytes for secondary batteries. However, such liquid electrolytes have problems such as the possibility of leakage to the outside of the secondary battery, reduced safety, and reduced cell rigidity.

[0006] In view of this, research is being conducted to commercialize polymer electrolytes such as gel polymer electrolytes instead of liquid electrolytes. The gel polymer electrolyte has the advantage of being able to prevent electrolyte leakage to the outside of the secondary battery and having excellent cell rigidity. However, the gel polymer electrolyte has problems such as high interface resistance and low ionic conductivity compared to liquid electrolytes.

[0007] On the other hand, in consideration of reducing the resistance and thermal stability of secondary batteries, a method of using lithium salts such as lithium bis(fluorosulfonyl)imide (LiFSI) has been considered. However, lithium salts such as lithium bis(fluorosulfonyl)imide have the problem of corroding the electrode tabs of secondary batteries, which is problematic in terms of long-term life characteristics. Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to solve the above problems, and to provide a method for manufacturing a secondary battery that reduces the resistance of the secondary battery, improves cell rigidity and thermal stability, and prevents corrosion of the electrode tabs, thereby being advantageous in terms of long life. [Means for solving the problem]

[0009] The present invention provides a method for producing a secondary battery, the method including the steps of (S1) accommodating an electrode assembly in a battery case, (S2) injecting a first electrolyte composition into the battery case to impregnate the electrode assembly, (S3) injecting a second electrolyte composition into the battery case, and (S4) curing the second electrolyte composition, wherein an electrode tab is connected to the electrode assembly and the electrode tab is extended to the outside of the electrode assembly, the first electrolyte composition includes a 1-1 lithium salt including at least one selected from the group consisting of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and a first solvent, the second electrolyte composition includes an oligomer and a second solvent, and the second electrolyte composition does not include lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). Effect of the Invention

[0010] The method for manufacturing a secondary battery according to the present invention is characterized by including a step of injecting an electrolyte composition in two steps. The first electrolyte composition is a liquid electrolyte composition or a gel polymer electrolyte composition, contains lithium bis(fluorosulfonyl)imide and / or lithium bis(trifluoromethanesulfonyl)imide as a lithium salt, is used for impregnating an electrode assembly, and helps to reduce the resistance and improve the thermal stability of the secondary battery. The second electrolyte composition does not contain lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide in the composition, and is cured outside the electrode assembly to form a gel polymer electrolyte. By the above-mentioned two-step electrolyte composition injection and curing process, lithium bis(fluorosulfonyl)imide and / or lithium bis(trifluoromethanesulfonyl)imide are arranged only inside the electrode assembly, and the resistance and thermal stability of the secondary battery can be reduced, the cell rigidity can be improved, leakage to the outside of the secondary battery can be prevented, and corrosion of the electrode tab can be prevented, thereby improving long-term life performance. [Brief description of the drawings]

[0011] [Figure 1] 2 is a plan view illustrating the electrode assembly housed in the battery case, illustrating step (S1) of the method for manufacturing a secondary battery according to the present invention. FIG. [Diagram 2] 1 is a side view illustrating the electrode assembly housed in the battery case, illustrating step (S1) of the method for manufacturing a secondary battery according to the present invention. FIG. [Diagram 3] 2 is a schematic side view of an electrode assembly for explaining step (S1) of the method for manufacturing a secondary battery according to the present invention. FIG. [Figure 4] FIG. 2 is a schematic side view of a separator for explaining step (S1) of the method for producing a secondary battery of the present invention. [Diagram 5] FIG. 2 is a schematic plan view of a separator or an electrode for explaining step (S1) of the method for producing a secondary battery of the present invention. [Figure 6] 1 is a diagram illustrating step (S1) of the method for manufacturing a secondary battery according to the present invention, and is a diagram illustrating a manufacturing process of an electrode assembly. [Figure 7] 1 is a diagram illustrating step (S1) of the method for manufacturing a secondary battery according to the present invention, and is a diagram illustrating a manufacturing process of an electrode assembly. [Figure 8] 1 is a diagram illustrating step (S1) of the method for manufacturing a secondary battery according to the present invention, and is a diagram illustrating a manufacturing process of an electrode assembly. [Figure 9] 1 is a diagram illustrating step (S1) of the method for manufacturing a secondary battery according to the present invention, and is a diagram illustrating a manufacturing process of an electrode assembly. [Figure 10] FIG. 2 is a plan view illustrating step (S2) of the method for producing a secondary battery of the present invention, and is a plan view illustrating a step of injecting a first electrolyte composition after step (S1). [Figure 11] FIG. 2 is a side view illustrating step (S2) of the method for producing a secondary battery of the present invention, and is a side view illustrating a step of injecting a first electrolyte composition after step (S1). [Figure 12] FIG. 2 is a plan view illustrating step (S3) of the method for producing a secondary battery of the present invention, and is a plan view illustrating a step of injecting a second electrolyte composition after step (S2). [Figure 13] FIG. 4 is a plan view illustrating step (S4) of the method for producing a secondary battery of the present invention, and is a plan view illustrating a hardening step of the second electrolyte composition after step (S3). [Figure 14] FIG. 2 is a side view illustrating step (S4) of the method for producing a secondary battery of the present invention, and is a side view illustrating a hardening step of the second electrolyte composition after step (S3). [Figure 15] 1 is a photograph of the surface of a separator included in a secondary battery produced by the production method of Example 1A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.

[0013] In this specification, the average particle size (D 50 The average particle size (D) can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured, for example, by using a laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to about several mm, and can provide results with high reproducibility and high resolution.

[0014] Hereinafter, the secondary battery of the present invention will be described in detail with reference to the drawings. When assigning reference numerals to components in each drawing, the same numerals may be assigned to the same components even if they are shown in different drawings. In addition, when describing the present invention, if it is determined that a detailed description of related known configurations or functions may obscure the gist of the present invention, the detailed description may be omitted.

[0015] <Secondary battery manufacturing method> The present invention relates to a method for manufacturing a secondary battery, and more particularly to a method for manufacturing a lithium secondary battery.

[0016] The present invention provides a method for producing a secondary battery, the method including: (S1) accommodating an electrode assembly in a battery case; (S2) injecting a first electrolyte composition into the battery case to impregnate the electrode assembly; (S3) injecting a second electrolyte composition into the battery case; and (S4) curing the second electrolyte composition, wherein an electrode tab is connected to the electrode assembly and the electrode tab is extended to the outside of the electrode assembly, the first electrolyte composition includes a 1-1 lithium salt including at least one selected from the group consisting of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and a first solvent, the second electrolyte composition includes an oligomer and a second solvent, and the second electrolyte composition does not include lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0017] (1) Electrode Assembly Storage Step (S1 Step) 1 and 2, the electrode assembly 100 is first housed in a battery case 300. Here, electrode tabs 400 and 500 are connected to the electrode assembly 100, and the electrode tabs 400 and 500 protrude to the outside of the electrode assembly 100.

[0018] The electrode assembly 100, the battery case 300, and the electrode tabs 400, 500 will be described below.

[0019] electrode assembly For convenience of explanation, FIGS. 1 and 2 simply show the configuration of the electrode assembly 100, and an exemplary configuration of the electrode assembly 100 can be described with reference to FIGS.

[0020] Referring to FIG. 3, the electrode assembly 100 may be manufactured by alternately stacking electrodes 110, 120 and separators 130, and applying an adhesive 140 to at least one surface of the electrodes 110, 120 and the separator 130 to adhere the electrodes 110, 120 and the separator 130 to each other.

[0021] The electrode assembly 100 includes a plurality of electrodes 110, 120 stacked in a vertical direction P. The number of the electrodes 110, 120 may be two or more. In this specification, the term "vertical direction" may refer to a vertical direction based on the ground and is intended to describe the stacking direction of the electrodes, and is not intended to limit the angle of the stacking direction.

[0022] The electrodes 110, 120 may include a first electrode 110 and a second electrode 120. As shown in FIG. 1, the first electrode 110 and the second electrode 120 may be alternately stacked. The electrodes 110, 120 may be alternately stacked with a separator 130 in between. The first electrode 110 may be a positive electrode and the second electrode 120 may be a negative electrode. Or the first electrode 110 may be a negative electrode and the second electrode 120 may be a positive electrode. There may be one or more first electrodes and two or more second electrodes, respectively.

[0023] The first electrode 110 and the second electrode 120 may have a structure in which an active material slurry is applied to a current collector. The first electrode 110 and the second electrode 120 may have a structure formed by applying the active material slurry to both sides of a current collector, drying, and rolling. The active material slurry may be formed by stirring a granular active material, a conductive material, a binder, and the like in a solvent. The first electrode 110 and the second electrode 120 may use, without limitation, an active material, a conductive material, a binder, and the like used for a positive electrode or a negative electrode in the art.

[0024] The current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity. Specifically, the current collector can include at least one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, sintered carbon, and aluminum-cadmium alloy. For example, when the electrodes 110 and 120 are positive electrodes, the current collector used for the electrodes 110 and 120 can include aluminum, and when the electrodes 110 and 120 are negative electrodes, the current collector used for the electrodes 110 and 120 can include copper.

[0025] The current collector can be used in various forms such as a film, a sheet, a foil, a net, a mesh, a porous body, a foam, a nonwoven fabric, etc. The current collector can include a polymer layer and a metal layer disposed on both sides of the polymer layer, and the metal layer can include at least one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, sintered carbon, and an aluminum-cadmium alloy.

[0026] Specifically, when the electrodes 110 and 120 are negative electrodes, the negative electrode active material contained therein may be, for example, a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, the carbon material may be either low crystalline carbon or high crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0027] Specifically, when the electrodes 110 and 120 are positive electrodes, the positive electrode active material contained therein is not particularly limited, and for example, the positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2Ni-site type lithium nickel oxide represented by the chemical formula LiMn 2-c3 Examples of the positive electrode include, but are not limited to, lithium manganese composite oxides represented by Mc3O2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be a metallic lithium (Li-metal) positive electrode.

[0028] Examples of binders contained in the electrodes include polyvinylidene fluoride polymer, polyvinyl alcohol, styrene butadiene rubber, polyethylene oxide, carboxyl methyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinylalcohol, cyanoethyl cellulose, and cyanoethyl sucrose. The binder polymer may be any one selected from the group consisting of sucrose, pullulan, polymethylmethacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, ethylene-vinyl acetate copolymer, polyarylate, and low molecular weight compounds having a molecular weight of 10,000 g / mol or less, or a mixture of two or more of these.

[0029] The conductive material contained in the electrode is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0030] An example of the thickener contained in the electrode is carboxymethyl cellulose (CMC).

[0031] 3, the electrode assembly 100 can include separators 130. The separators are stacked alternately with the electrodes.

[0032] As shown in FIG 3, the separator 130 may be bent or folded in a zigzag shape to wrap one end of the electrodes 110, 120. For example, as shown in FIG 1, when the first electrode 110 and the second electrode 120 are alternately stacked, the separator 130 may be folded to wrap one end 110a of the first electrode 110, and then folded again to wrap one end 110a of the second electrode 110 that is opposite to the one end 110a of the first electrode 110. As this folding is repeated, the separator 130 may be bent or folded in a zigzag shape. The electrode assembly 100 may include one separator 130.

[0033] The electrode assembly 100 may be a zigzag stack type electrode assembly in which the separator 130 is bent or folded in a zigzag shape, and one or more basic units, in particular two or more basic units, in which the first electrode 110, the separator 130, the second electrode 120 and the separator 130 are stacked in order, are stacked.

[0034] As shown in FIG. 4, the separator 130 may include a porous substrate 131 and ceramic coating layers 132a, 132b disposed on both sides of the porous substrate.

[0035] The porous substrate 131 is not particularly limited as long as it is normally used as a separator for a secondary battery. Specifically, the porous substrate 131 is preferably one that has low resistance to ion migration of an electrolyte and has excellent electrolyte moisture absorption ability. More specifically, the porous substrate 131 may contain at least one selected from the group consisting of polyolefin resins such as polyethylene, polypropylene, polybutylene, and polypentene; fluorine resins such as polyvinylidene fluoride and polytetrafluoroethylene; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; polyacrylonitrile resins; and cellulose resins, and may be a porous film or nonwoven fabric containing one or more of these, or a copolymer or mixture thereof, or a laminate structure of two or more layers thereof. The porous substrate 131 may be a porous film, nonwoven fabric, or a laminate structure of two or more layers thereof containing the polyolefin resin.

[0036] The size and porosity of the pores present in the porous substrate 131 are not particularly limited. Specifically, the porous substrate 131 may be a porous substrate containing pores having an average pore diameter of 0.01 μm to 1 μm, specifically 20 nm to 60 nm, with a porosity of 10 vol% to 90 vol%, specifically 30 vol% to 60 vol%, in which case it is preferable in terms of improving the mechanical strength of the porous substrate 131 and allowing ionic substances to move more smoothly between the positive and negative electrodes. The average pore diameter and porosity may be measured by analysis using a focused ion beam (FIB), a gas adsorption method, or a mercury intrusion method.

[0037] The thickness of the porous substrate 131 is not particularly limited, but may be, in consideration of appropriate mechanical strength as a separator and ease of movement of ionic substances, specifically, 1 μm to 100 μm, more specifically, 2 μm to 15 μm.

[0038] The ceramic coating layers 132 a and 132 b are disposed on both sides of the porous substrate 131 .

[0039] The ceramic coating layers 132a and 132b include inorganic particles and a binder. More specifically, the ceramic coating layers may consist of only the inorganic particles and the binder.

[0040] The inorganic particles may be introduced to prevent thermal shrinkage of the porous substrate at high temperatures and the resulting short circuit between the positive and negative electrodes, and the inorganic particles may serve as a kind of spacer that can maintain the physical shape of the porous substrate and minimize thermal shrinkage.

[0041] The inorganic particles are preferably those having a voltage range within the operating voltage range of the battery (e.g., Li / Li +It can be used without particular limitation as long as it is electrochemically stable in the range of 0 V to 5 V with respect to the reference and does not cause oxidation and / or reduction reactions, that is, electrochemical reactions. The inorganic particles include lithium phosphate (Li3PO4); lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3); lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y -based glass (glass) (0 < x < 4, 0 < y < 13); lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3); Li 3.25 Ge 0.25 P 0.75 S4 and other lithium germanium thiophosphates (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5); lithium nitrides such as Li3N (Li x N y , 0 < x < 4, 0 < y < 2); SiS2-based glasses such as Li3PO4-Li2S-SiS2 (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4); P2S5-based glasses such as LiI-Li2S-P2S5 (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7); Al2O3; AlOOH; BaTiO3; BaSO4; MgO; CaO; CeO2; NiO; SiO2; SnO2; SrTiO3; TiO2; Y2O3; ZnO; ZrO2; Pb(Zr, Ti)O3 (PZT); Pb 1-x La x Zr 1-y Ti y O3 (PLZT); PB(Mg3Nb 2 / 3)O3-PbTiO3 (PMN-PT); hafnia (HfO2); a mixture of two or more of these. Specifically, the inorganic particles may be Al2O3; AlOOH; BaTiO3; BaSO4; MgO; CaO; CeO2; NiO; SiO2; SnO2; SrTiO3; TiO2; Y2O3; ZnO; ZrO2; Pb(Zr,Ti)O3 (PZT); Pb 1-x La x Zr 1-y Ti y O3(PLZT);PB(Mg3Nb 2 / 3 )O3-PbTiO3 (PMN-PT); hafnia (HfO2); a mixture of two or more of these, and more specifically, it may include at least one selected from the group consisting of Al2O3; AlOOH; BaTiO3; BaSO4; and MgO.

[0042] The average particle size of the inorganic particles (D 50 ) can be 0.1 μm to 1 μm, specifically 0.2 μm to 0.7 μm.

[0043] The inorganic particles are included in the ceramic coating layers 132a and 132b in an amount of 92% by weight or more and less than 100% by weight. The content of the inorganic particles should be considered in relation to the content of the binder described below, and can be adjusted to prevent a decrease in thermal stability due to thermal contraction of the porous substrate and to prevent an increase in resistance due to an excessive amount of binder. Specifically, the inorganic particles can be included in the ceramic coating layers in an amount of 93% by weight to 98% by weight.

[0044] The binder may be included in the ceramic coating layers 132a and 132b to bind inorganic particles and to bind the separator and electrodes.

[0045] Here, the binder is contained in the ceramic coating layer in an amount of more than 0 wt % and less than 8 wt %. If the binder is contained in an amount of more than 8 wt %, the binder is excessively contained in the ceramic coating layer, which may cause an increase in the resistance of the secondary battery. On the other hand, if the binder is contained in the above range, there is a risk of a decrease in the cell rigidity of the secondary battery due to a decrease in the adhesive strength between the electrode and the separator. However, as described below, the present invention uses a combination of a separator having the above characteristics and a gel polymer electrolyte, and therefore can simultaneously achieve an improvement in the resistance of the secondary battery, as well as an improvement in cell rigidity and mechanical durability.

[0046] Specifically, the binder may be included in the ceramic coating layer in an amount of 2 wt % to 7 wt %, and when the amount is within this range, the binding force of the inorganic particles can be maximized and an increase in the resistance of the secondary battery can be prevented.

[0047] The binder may be a hydrophobic binder containing one or more hydrophobic functional groups in the molecule, such as a fluorine group (-F), an acrylate group (CH2=CHCOO-), a methacrylate group (CH2=C(CH3)COO-), a vinyl acetate group (-CH2=CHOCO-) or a nitrile group (-C≡N), or a hydrophilic binder containing one or more polar groups, such as a hydroxyl group (-OH), a carboxyl group (-COOH), a maleic anhydride group (-COOOC-), a sulfonic acid group (-SO3H) or an isocyanate group (-NCO-), and any one or a mixture of two or more of these may be used. More specifically, the hydrophobic binder may be polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polyacrylonitrile, polyvinylacetate, ethylene-vinylacetate copolymer, polyimide, polyethylene oxide, or the like.In addition, the hydrophilic binder may be cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, carboxyl methyl cellulose, polyvinyl alcohol, polyacrylic acid, polymaleic anhydride, polyvinylpyrrolidone, or the like.

[0048] Specifically, the binder may be an acrylic binder. The acrylic binder allows the inorganic particles to be well dispersed during the preparation of the ceramic coating layer, thereby preventing the ceramic coating layer from being separated into layers, with the binder in the upper layer and the inorganic particles in the lower layer. Such layer separation results in impeding ion migration in the negative and positive electrodes, causing an increase in resistance. Therefore, when an acrylic binder is used as the binder, the resistance reduction effect aimed at by the present invention can be exhibited at a more excellent level.

[0049] The acrylic binder may include at least one selected from the group consisting of a copolymer of ethylhexyl acrylate and methyl methacrylate; polymethylmethacrylate; polyethylhexylacrylate; polybutylacrylate; polyacrylonitrile; and a copolymer of butyl acrylate and methyl methacrylate.

[0050] The ceramic coating layer may contain inorganic particles and a binder in a weight ratio of 92:8 or more and less than 100:0, specifically 93:7 to 98:2.

[0051] The ceramic coating layers 132a and 132b may have a thickness of 0.1 μm to 10 μm, specifically 0.5 μm to 5 μm, and more specifically 1.0 μm to 2.5 μm. Since the ceramic coating layers 132a and 132b contain the binder in the above-mentioned small content, a separator with a thin thickness can be realized, and the energy density of the secondary battery can be further improved and low resistance can be realized. The thickness of the ceramic coating layer may refer to the thickness of one ceramic coating layer formed on one surface of the porous substrate.

[0052] The ceramic coating layers 132a and 132b may be prepared by applying a ceramic coating layer forming composition, in which inorganic particles and a binder are dispersed in a solvent, to the porous substrate and drying the composition. The method of applying the ceramic coating layer forming composition is not particularly limited, and may be dip coating, die coating, roll coating, comma coating, gravure coating, etc., and more specifically, gravure coating may be used. The drying method after application of the ceramic coating layer forming composition may be natural drying, heat drying, hot air drying, etc.

[0053] The thickness of the separator 130 may be 1 μm to 20 μm, specifically 5 μm to 14 μm. According to the present invention, since the binder content in the ceramic coating layer is reduced, a separator with a thin thickness can be realized, and thus the energy density of the secondary battery can be further improved and low resistance can be achieved.

[0054] As described above, since the ceramic coating layer included in the separator contains a small amount of binder, an increase in resistance due to an excessive amount of binder can be prevented. Meanwhile, in the case of the secondary battery according to the present invention, since a gel polymer electrolyte is used as the electrolyte, the gel polymer electrolyte can compensate for the decrease in cell rigidity of the secondary battery that accompanies the decrease in resistance. Therefore, the secondary battery manufactured by the manufacturing method of the secondary battery according to the present invention can simultaneously reduce the resistance of the secondary battery and improve the cell rigidity and mechanical durability by combining the above-mentioned components.

[0055] As shown in Figures 3 and 5, the electrode assembly 100 may have an adhesive 140 applied to a surface of at least one of the electrodes 110, 120 and the separator 130, so that the electrodes 110, 120 and the separator 130 are adhered to each other.

[0056] The adhesive 140 may be introduced to bond the electrodes 110, 120 and the separator 130. Specifically, the adhesive may be introduced to fix the alignment position of the electrodes and the separator in the process of laminating, assembling, and stacking them in the manufacturing process of the secondary battery. As described above, the separator 130 according to the present invention may have insufficient adhesive strength between the electrodes and the separator during the manufacturing of the secondary battery due to the reduced binder content, and the adhesive 140 compensates for this problem, easily bonds the electrodes and the separator, prevents the separator from shifting during the manufacturing process of the electrode assembly, and improves the efficiency and quality of the process.

[0057] The adhesive may be an acrylate adhesive, and by using the acrylate adhesive, the adhesive can be easily dissolved and removed.

[0058] Specifically, the acrylate adhesive may include a copolymer including repeat units derived from at least one monomer selected from the group consisting of methyl methacrylate (MMA), 2-ethylhexyl acrylate (2-EHA), and 2-hydroxyethyl acrylate (2-HEA).

[0059] The weight average molecular weight (Mw) of the copolymer may be 120,000 g / mol to 140,000 g / mol. The molecular weight of the copolymer can be measured by a conventional method well known in the art. For example, the molecular weight can be measured by a terminal group quantitative analysis of functional groups at the molecular chain end to determine the molecular weight, a generalized method using physical properties such as osmotic pressure, vapor pressure depression, boiling point elevation, and freezing point depression (separator permeation method, vapor pressure osmometry, etc.), a light scattering method using light scattering, an ultracentrifugation method in which a polymer solution is centrifuged and then the sedimentation velocity or concentration distribution is analyzed to measure the molecular weight, a viscosimetry using the viscosity of the polymer solution, gel permeation chromatography (GPC) using high performance liquid chromatography (HPLC), etc. can be used.

[0060] The adhesive is used to manufacture an electrode assembly by adhering an electrode and a separator, and the electrode assembly is housed in a battery case, and a first electrolyte composition and / or a second electrolyte composition, specifically the first electrolyte composition, described below is injected into the battery case, and the adhesive can be dissolved in an organic solvent contained in the first electrolyte composition and / or the second electrolyte composition, specifically the first electrolyte composition. Since the adhesive according to the present invention is dissolved and removed after being used to manufacture the electrode assembly, it is possible to easily adhere the electrode and the separator without increasing the amount of binder in the separator, and also to prevent an increase in the thickness of the separator due to an increase in the amount of binder, thereby further improving the energy density of the secondary battery.

[0061] The adhesive may be applied in a plurality of patterns spaced apart from one another. Specifically, the adhesive may be applied on a surface of at least one of the electrodes and the separator in a plurality of patterns spaced apart from one another. Specifically, the adhesive may be applied on a surface of at least one of the electrodes and the separator in a plurality of dots spaced apart from one another.

[0062] The adhesive is removed by injecting a first electrolyte composition, which will be described later, and a trace of the adhesive application may remain on the surface of at least one of the electrodes 110, 120 and the separator 130. Specifically, when the first electrolyte composition is injected into a battery case housing the electrode assembly, the adhesive is dissolved and removed by an organic solvent in the first electrolyte composition, and may leave a trace of the adhesive application.

[0063] The adhesive application area may be more than 0% and 1% or less, specifically 0.0001% to 0.05%, of the surface area where the separator and the electrode contact each other. This range is preferable because it allows the electrodes and the separator to be bonded with sufficient adhesive strength and prevents the adhesive from being applied in excess and remaining in the solvent without being dissolved, which causes an increase in resistance.

[0064] An exemplary method for manufacturing the electrode assembly will now be described with reference to FIGS.

[0065] Specifically, referring to Figures 6 to 9, the electrodes 110, 120 include a first electrode 110 and a second electrode 120, and the electrode assembly 100 can be manufactured by a method including the following steps (a) to (d).

[0066] (a) applying the adhesive 140 to at least a portion of the separator 130 and the first electrode 110; (b) adhering the separator 130 and the first electrode 110 with the applied adhesive 140; (c) folding one side of the separator 130 to cover the first electrode 110; (d) applying the adhesive 140 to at least a portion of the separator 130 and the second electrode 120; (e) adhering the separator 130 and the second electrode 120 with the applied adhesive 140; and (d) folding the other side of the separator 130 to cover the second electrode 120 .

[0067] 6, the adhesive 140 is applied to at least a portion of the separator 130 and the first electrode 110. The application of the adhesive 140 may be performed by applying the adhesive 140 to at least a portion of the separator 130 and the first electrode 110 using a first nozzle 1110. Although FIG. 6 illustrates the adhesive 140 being applied to the separator 130, the present invention is not limited thereto, and the adhesive 140 may be applied to at least a portion of the separator 130; the first electrode 110; or both the separator 130 and the first electrode 110.

[0068] Specifically, as shown in FIG. 6, the separator 130 may be unwound from a separator reel 630 and placed on the upper surface of a table 700 .

[0069] Referring to FIG. 7, the separator 130 and the first electrode 110 are bonded together by the applied adhesive 140 .

[0070] 9, the first electrode 110 may be formed by cutting a first electrode sheet 1101, which is wound from a first electrode reel 610, by a first cutter 810. Here, when a first transfer device 910 transfers the first electrode 110, a first header 1010 may adsorb the first electrode. Next, the first electrode 110 may be placed or disposed on the separator 130 as the first header 1010 and / or the table 700 move.

[0071] Referring to FIG. 8, one side of the separator 130 may be folded to cover the first electrode 110, and the adhesive 140 may be applied to at least a portion of the separator 130 and the second electrode 120.

[0072] After the first electrode 110 is attached on the separator 130, one side of the separator 130 is folded to cover the first electrode 110. For example, the separator 130 may be folded by moving the table 700 laterally.

[0073] Meanwhile, the adhesive 140 is applied to at least a portion of the separator 130 and the second electrode 120. The application of the adhesive 140 may be performed by applying the adhesive 140 to at least a portion of the separator 130 and the second electrode 120 using a second nozzle 1120. Although FIG. 8 illustrates the adhesive 140 being applied to the separator 130, the present invention is not limited thereto, and the adhesive 140 may be applied to at least a portion of the separator 130; the second electrode 120; or both the separator 130 and the second electrode 120.

[0074] Referring to FIG. 9, the separator 130 and the second electrode 120 are adhered to each other by the applied adhesive 140, and the other side of the separator 130 is folded to cover the second electrode 120.

[0075] A second electrode 120 is attached to the surface of the separator 130 opposite to the surface where the separator 130 and the first electrode 110 are in contact.

[0076] 9, the second electrode 120 may be formed by cutting a first electrode sheet 1201 unwound from a second electrode reel 620 by a second cutter 820. Here, when a second transport device 920 transports the second electrode 120, a second header 1020 may adsorb the second electrode. Then, as the second header 1020 and / or the table 700 move, the second electrode may be placed or adhered on the separator.

[0077] 9, after the second electrode 120 is attached, the other side of the separator 130 is folded to cover the second electrode 120. This makes it possible to manufacture an electrode assembly in which the first and second electrodes are alternately stacked, the separator is interposed between the first and second electrodes, and the separator is folded in a zigzag shape. Next, by repeating the above process, an electrode assembly in which a plurality of first electrodes and second electrodes are alternately stacked can be realized.

[0078] Here, in the case of an electrode assembly including a separator folded in a zigzag shape as described above, the separator and / or electrode may be misaligned due to the folding or bending of the separator during the manufacturing process, which may lead to poor quality and reduced process efficiency, but according to the present invention, an adhesive is applied to bond the electrode and the separator, which significantly prevents the above-mentioned misalignment of the electrode and / or separator, making it possible to manufacture a secondary battery with improved quality. The application of such an adhesive is particularly preferable in terms of complementing the adhesive strength of the separator in the present invention, which contains a low content of binder.

[0079] Electrode Tab As shown in FIGS. 1 and 2, electrode tabs 400 and 500 are connected to the electrode assembly 100, and the electrode tabs 400 and 500 protrude to the outside of the electrode assembly 100.

[0080] There may be a plurality of electrode tabs 400, 500. Specifically, the plurality of electrode tabs 400, 500 are connected to the electrodes 110, 120 of the electrode assembly 100, more specifically, to the first electrode 110 and the second electrode 120, respectively, and may protrude to the outside of the battery case 300 to serve as a path for electron movement. In addition, although the two electrode tabs 400, 500 are illustrated in Figs. 1 and 2 as being arranged in different directions with respect to the electrode assembly 100, the present invention is not limited thereto, and they may protrude in parallel in the same direction from one side of the electrode assembly 100.

[0081] The plurality of electrode tabs 400, 500 may be positive electrode tabs and negative electrode tabs, and may be connected to positive and negative electrodes, respectively.

[0082] The electrode tab may include aluminum. As described below, the first electrolyte composition including at least one selected from the group consisting of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide does not contact the electrode tab, so that the electrode tab is less likely to be damaged due to corrosion of aluminum, and the long-term life characteristics can be improved.

[0083] Specifically, the electrode tabs may include a positive electrode tab and a negative electrode tab, the positive electrode tab may include aluminum, and the negative electrode tab may include nickel.

[0084] Battery case The battery case 300 may be provided for the purpose of housing the electrode assembly 100. In addition, in the battery case 300, a first electrolyte composition 210 (described later) may be disposed inside the electrode assembly 100, and a second electrolyte composition 220 (described later) may be cured and disposed outside the electrode assembly 100.

[0085] The battery case 300 may be a pouch-shaped case made of a flexible material, for example, an aluminum pouch battery case.

[0086] When the battery case 300 is an aluminum pouch battery case, the battery case 300 can be formed of a pouch film in which, for example, a polypropylene layer (PP layer), an aluminum layer, and a polyethylene terephthalate layer (PET layer) are laminated in this order from the inside.

[0087] The battery case 300 may include a cup portion 310 that is a receiving space for receiving the electrode assembly.

[0088] The battery case 300 may include a cover 320, and after the electrode assembly is housed and the gel polymer electrolyte composition is hardened and gelled, the battery case 300 may be sealed with the cover to manufacture a sealed secondary battery.

[0089] (2) Injection of the first electrolyte composition and impregnation of the electrode assembly (S2 step) 10 and 11, a first electrolyte composition 210 is injected into the battery case 300 to impregnate the electrode assembly 100. Here, the first electrolyte composition 210 includes a 1-1 lithium salt including lithium bis(fluorosulfonyl)imide, a first oligomer, and a first solvent.

[0090] The first electrolyte composition 210 is introduced to impregnate the electrode assembly 100 and to be disposed inside the electrode assembly 100 .

[0091] Specifically, the first electrolyte composition 210 may be injected so as not to come into contact with the electrode tabs 400, 500 disposed outside the electrode assembly 100. This can prevent lithium bis(fluorosulfonyl)imide contained in the first electrolyte composition 210 from coming into contact with the electrode tabs 400, 500, specifically, the electrode tabs 400, 500 containing aluminum, causing corrosion.

[0092] The first electrolyte composition 210 is injected into the electrode assembly 100 to impregnate the electrode assembly 100. Specifically, the first electrolyte composition 210 may be injected in an amount calculated in advance in consideration of the size, volume, etc. of the electrode assembly 100 in order to impregnate the electrode assembly 100 without contacting the electrode tabs 400 and 500.

[0093] The impregnation of the first electrolyte composition 210 may be performed at a temperature of 10° C. to 30° C. for 0.5 to 72 hours, and preferably at a temperature of 15° C. to 30° C. for 40 to 65 hours.

[0094] The first electrolyte composition 210 includes a 1-1 lithium salt including at least one selected from the group consisting of lithium bis(fluorosulfonyl)imide (LiFSI, LiN(FSO2)2) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, LiN(CF3SO2)2), a first oligomer, and a first solvent.

[0095] The lithium bis(fluorosulfonyl)imide and / or lithium bis(trifluoromethanesulfonyl)imide that may be contained in the 1-1 lithium salt is injected into the inside of the electrode assembly, and therefore has the advantage of not only reducing the resistance of the electrode assembly but also improving the thermal stability of the secondary battery. Meanwhile, the second electrolyte composition that is injected and disposed outside the electrode assembly does not contain lithium bis(fluorosulfonyl)imide, and therefore the possibility of lithium bis(fluorosulfonyl)imide coming into contact with the electrode tabs 400, 500 is significantly reduced, and corrosion of the electrode tabs can be prevented.

[0096] The 1-1 lithium salt may be included in the first electrolyte composition at a molar concentration of 0.5M or more, specifically 0.65M or more. When it is in this range, the effect of reducing the resistance of the secondary battery and improving the thermal stability may be more preferably realized. The upper limit of the molar concentration of the 1-1 lithium salt is not particularly limited, and may be 5M or less in terms of easy dissolution of the 1-1 lithium salt. In this specification, the molar concentration means the molar content of a component relative to the volume of the composition, and the unit "M" of "molar concentration" may mean "mol / L".

[0097] The first electrolyte composition may further contain a 1-2 lithium salt together with the 1-1 lithium salt for the purpose of further reducing resistance and preventing corrosion.

[0098] The first and second lithium salts are lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroantimonate (LiSbF6), lithium tetraoxoaluminate (LiAlO4), lithium tetrachloroaluminate (LiAlCl4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium nonafluorobutanesulfonate (LiC 4F9SO3), lithium chloride (LiCl), lithium iodide (LiI), lithium bis(oxalato)borate (LiBOB, LiB(C2O4)2), lithium bis(pentafluoroethanesulfonyl)imide (LiBETI, LiN(C2F5SO2)2), lithium fluoroalkylborate (LiFAB), and lithium 2-trifluoromethyl-4,5-dicyanoimidazole (LiTDI), and specifically, LiPF6 may be included.

[0099] In the first electrolyte composition, the ratio of the molar concentration of the 1-1 lithium salt to the molar concentration of the 1-2 lithium salt may be 0.9:1 to 10:1, and when it is in this range, the resistance of the secondary battery can be improved and the thermal stability of the secondary battery can be improved to a preferable level. In the first electrolyte composition, the ratio of the molar concentration of the 1-1 lithium salt to the molar concentration of the 1-2 lithium salt may be more specifically 0.9:1 to 5:1, and even more specifically 0.9:1 to 1.2:1.

[0100] The ratio of the molar concentration of the 1-1 lithium salt to the molar concentration of the 1-2 lithium salt may be 1.1 or more, and when it is in this range, the resistance of the secondary battery can be improved and the thermal stability of the secondary battery can be improved to a preferred level. More specifically, the ratio of the molar concentration of the 1-1 lithium salt to the molar concentration of the 1-2 lithium salt may be 2.5 or more. The upper limit of the ratio of the molar concentration of the 1-1 lithium salt to the molar concentration of the 1-2 lithium salt is not particularly limited and may be 10 or less, specifically 5 or less.

[0101] In the first electrolyte composition, the sum of the molar concentrations of the 1-1 lithium salt and the 1-2 lithium salt may be 0.7M or more, specifically 1.2M or more. When it is in this range, the resistance of the secondary battery can be improved and the thermal stability of the secondary battery can be improved to a preferable level. The upper limit of the sum of the molar concentrations of the 1-1 lithium salt and the 1-2 lithium salt is not particularly limited, and may be 5M or less, specifically 1.8M or less.

[0102] The first solvent may be used to dissolve or disperse the first-1 lithium salt. The first solvent may be an organic solvent.

[0103] The first solvent is one that is commonly used in secondary batteries, and for example, ethers, esters (acetates, propionates), amides, linear or cyclic carbonates, nitriles (acetonitrile, SN, etc.), etc., can be used alone or in combination of two or more.

[0104] Among them, typically, carbonate-based solvents containing a carbonate compound such as a cyclic carbonate, a linear carbonate, or a mixture thereof can be used as the first solvent.

[0105] Specific examples of the cyclic carbonate compound include a single compound or a mixture of at least two selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, and halides thereof. Specific examples of the linear carbonate compound include a compound or a mixture of at least two selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC), but are not limited thereto.

[0106] In particular, among the carbonate-based solvents, propylene carbonate and ethylene carbonate, which are cyclic carbonates, are preferably used since they are high-viscosity organic solvents with high dielectric constants and can easily dissociate lithium salts in the electrolyte. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as ethyl methyl carbonate, diethyl carbonate, or dimethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be obtained, and therefore the mixture can be more preferably used.

[0107] In addition, the ester of the first solvent may be a single compound or a mixture of at least two kinds selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, α-valerolactone, and ε-caprolactone, but is not limited thereto.

[0108] The first electrolyte composition 210 can be a liquid electrolyte composition or a gel polymer electrolyte composition.

[0109] When the first electrolyte composition 210 is a liquid electrolyte composition, the first electrolyte composition 210 may be free of oligomers for the formation of a gel polymer electrolyte.

[0110] When the first electrolyte composition 210 is a gel polymer electrolyte composition, the first electrolyte composition may further include an oligomer. The oligomer may include at least one selected from the group consisting of polyether-based oligomers, polycarbonate-based oligomers, acrylate-based oligomers, polysiloxane-based oligomers, phosphagene-based oligomers, polyethylene-based oligomers, urethane-based oligomers, epoxy-based oligomers, fluorine-based oligomers, polyethylene oxide, polyester sulfide, polyvinyl alcohol, and polyvinylidene fluoride, specifically at least one selected from fluorine-based oligomers, polycarbonate-based oligomers, and polysiloxane-based oligomers.

[0111] For example, the fluorine-based oligomer may specifically include a unit derived from a fluorine-based monomer. The fluorine-based oligomer has an advantage that the fluorine-based functional group contained therein suppresses the generation of oxygen radicals caused by the decomposition of the positive electrode active material, thereby further improving battery stability and having excellent flame retardancy. More specifically, the fluorine-based oligomer may include at least one selected from tetrafluoroethylene (TFE)-vinyl acetate copolymer, (allyl 1,1,2,2-tetrafluoroethyl ether)-(2,2,2-trifluoroethyl acrylate) copolymer, tetrafluoroethylene-(2-vinyl-1,3-dioxolane) copolymer, and tetrafluoroethylene-vinyl methacrylate copolymer.

[0112] In addition, the polycarbonate oligomer has an affinity with the positive electrode, a structure similar to that of an organic electrolyte, and an advantage in that it has excellent ion conductivity or ion dissociation degree. The polycarbonate oligomer may be a polycarbonate having a weight average molecular weight of 1,000 g / mol to 50,000 g / mol, specifically 4,500 g / mol to 30,000 g / mol, more specifically 10,000 g / mol to 25,000 g / mol.

[0113] In addition, the polysiloxane oligomer can function as a scavenger for gases (such as HF) generated by side reactions of the electrolyte, thereby improving high-temperature storage characteristics.

[0114] The weight average molecular weight of the oligomer can be from 1,000 g / mol to 50,000 g / mol, specifically from 4,500 g / mol to 30,000 g / mol.

[0115] The oligomer may be included in the first electrolyte composition in an amount of 0.1 wt % to 30 wt %, specifically 1 wt % to 10 wt %, and when it is in this range, the ionic conductivity and lithium ion mobility of the gel polymer electrolyte may be exhibited at an excellent level.

[0116] When the first electrolyte composition 210 is a gel polymer electrolyte composition, the first electrolyte composition 210 may be cured after the step (S2), if necessary.

[0117] This step is not essential, and after the injection of the second electrolyte composition, the first electrolyte composition 210 and the second electrolyte composition 220 may be cured together in step (S4) as described below. However, when the curing process is performed after the impregnation of the first electrolyte composition 210, there is an advantage in that the first electrolyte composition 210 is prevented from flowing out of the electrode assembly 100 before the injection of the second electrolyte composition 220, and the first electrolyte composition 210 and the second electrolyte composition 220 are prevented from being mixed with each other.

[0118] Here, the curing may be performed at a temperature of 50° C. to 100° C. for 0.5 to 48 hours, and preferably at a temperature of 60° C. to 80° C. for 0.5 to 24 hours.

[0119] In the case where the first electrolyte composition 210 is cured after the step (S2), the first electrolyte composition 210 may further include a polymerization initiator for polymerizing and crosslinking the oligomer. The types of polymerization initiators will be described later.

[0120] (3) Injection of second electrolyte composition (S3 step) 12, after step (S2), a second electrolyte composition 220 is injected into the battery case 300. Here, the second electrolyte composition 220 includes an oligomer and a second solvent, and does not include lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide.

[0121] 12, the second electrolyte composition 220 injected into the battery case 300 may be injected outside the electrode assembly 100. The second electrolyte composition 220 does not include lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide, and therefore may not cause a corrosion problem in the electrode tabs 400 and 500 present outside the electrode assembly 100.

[0122] The second electrolyte composition 220 includes an oligomer and a second solvent. The second electrolyte composition includes the oligomer, so that the second electrolyte composition can form a gel polymer electrolyte 220a.

[0123] The oligomer can be polymerized and crosslinked by a curing process of the second electrolyte composition.

[0124] The oligomer may include at least one selected from the group consisting of polyether-based oligomers, polycarbonate-based oligomers, acrylate-based oligomers, polysiloxane-based oligomers, phosphagene-based oligomers, polyethylene-based oligomers, urethane-based oligomers, epoxy-based oligomers, fluorine-based oligomers, polyethylene oxide, polyester sulfide, polyvinyl alcohol, and polyvinylidene fluoride, specifically at least one selected from fluorine-based oligomers, polycarbonate-based oligomers, and polysiloxane-based oligomers.

[0125] For example, the fluorine-based oligomer may specifically include a unit derived from a fluorine-based monomer. The fluorine-based oligomer has an advantage that the fluorine-based functional group contained therein suppresses the generation of oxygen radicals caused by the decomposition of the positive electrode active material, thereby further improving battery stability and having excellent flame retardancy. More specifically, the fluorine-based oligomer may include at least one selected from tetrafluoroethylene (TFE)-vinyl acetate copolymer, (allyl 1,1,2,2-tetrafluoroethyl ether)-(2,2,2-trifluoroethyl acrylate) copolymer, tetrafluoroethylene-(2-vinyl-1,3-dioxolane) copolymer, and tetrafluoroethylene-vinyl methacrylate copolymer.

[0126] In addition, the polycarbonate oligomer has an affinity with the positive electrode, a structure similar to that of an organic electrolyte, and an advantage in that it has excellent ion conductivity or ion dissociation degree. The polycarbonate oligomer may be a polycarbonate having a weight average molecular weight of 1,000 g / mol to 50,000 g / mol, specifically 4,500 g / mol to 30,000 g / mol, more specifically 10,000 g / mol to 25,000 g / mol.

[0127] In addition, the polysiloxane oligomer can function as a scavenger for gases (such as HF) generated by side reactions of the electrolyte, thereby improving high-temperature storage characteristics.

[0128] The weight average molecular weight of the oligomer can be from 1,000 g / mol to 50,000 g / mol, specifically from 4,500 g / mol to 30,000 g / mol.

[0129] The oligomer may be included in the second electrolyte composition in an amount of 0.1 wt % to 30 wt %, specifically 1 wt % to 10 wt %, and when it is in this range, the second electrolyte composition disposed outside the electrode assembly is cured, thereby improving the rigidity of the secondary battery, preventing leakage of the secondary battery, and further improving the safety of the secondary battery.

[0130] The type of the second solvent may be the same as that exemplified for the first solvent, although the first and second solvents may be the same or different.

[0131] The second electrolyte composition 220 may further include a second lithium salt to improve the resistance of the secondary battery.

[0132] The second lithium salt may be lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroantimonate (LiSbF6), lithium tetraoxoaluminate (LiAlO4), lithium tetrachloroaluminate (LiAlCl4), lithium trifluoromethanesulfonate (LiCF3SO3), or lithium nonafluorobutanesulfonate. (LiC4F9SO3), lithium chloride (LiCl), lithium iodide (LiI), lithium bis(oxalato)borate (LiBOB, LiB(C2O4)2), lithium bis(pentafluoroethanesulfonyl)imide (LiBETI, LiN(C2F5SO2)2), lithium fluoroalkylborate (LiFAB) and lithium 2-trifluoromethyl-4,5-dicyanoimidazole (LiTDI), specifically, at least one selected from the group consisting of LiPF6. Here, the second lithium salt may be free of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide in terms of preventing corrosion of the electrode tab.

[0133] The second lithium salt may be contained in the second electrolyte composition at a molar concentration of 0.1M to 3.0M, specifically, at a molar concentration of 0.5M to 1.5M, in order to improve the resistance of the secondary battery.

[0134] (4) Hardening of the second electrolyte composition (Step S4) 13 and 14, the second electrolyte composition 220 is cured. The second electrolyte composition 220 injected into the battery case 300 can be cured to form a gel polymer electrolyte 220a. When the first electrolyte composition 210 is a gel polymer electrolyte composition, both the first electrolyte composition 210 and the second electrolyte composition 220 can be cured in step (S4).

[0135] As shown in Figures 13 and 14, after step (S4), the first electrolyte composition may be disposed inside the electrode assembly. If the first electrolyte composition is a liquid electrolyte composition, it may be disposed in a state of being impregnated inside the electrode assembly. Alternatively, if the first electrolyte composition is a gel polymer electrolyte composition, it may be hardened and disposed inside the electrode assembly in the form of a gel polymer electrolyte 210a. The gel polymer electrolyte 220a formed from the second electrolyte composition 220 may be disposed outside the electrode assembly 100.

[0136] The curing of the second electrolyte composition 220 or the first electrolyte composition 210 and the second electrolyte composition 220 may be performed by a photocuring or thermal curing process, and specifically, may be performed by a thermal curing process.

[0137] The second electrolyte composition 220, or the first electrolyte composition 210 and the second electrolyte composition 220, can be cured in the presence of a polymerization initiator. The polymerization initiator can be used to polymerize the oligomers contained in the electrolyte composition to form a polymer network connected in a three-dimensional structure.

[0138] The polymerization initiator may be included in the second electrolyte composition 220. A curing process may be performed on the second electrolyte composition by forming radicals from the polymerization initiator.

[0139] Meanwhile, the polymerization initiator may not be included in the second electrolyte composition 220, but may be added to the battery case 300 in a separate process to help harden the second electrolyte composition 220. Specifically, the method for manufacturing a secondary battery of the present invention may further include a step of injecting a polymerization initiator into the battery case 100 before performing step (S4), specifically, before performing step (S4) after performing step (S3). This is preferable in that pre-gelation, in which the second electrolyte composition hardens due to radicals randomly generated without a polymerization initiator, can be prevented, and sufficient impregnation of the electrode assembly and smooth control of the secondary battery manufacturing process can be achieved.

[0140] The polymerization initiator may be a photopolymerization initiator or a thermal polymerization initiator depending on the polymerization method.

[0141] Specifically, the photopolymerization initiator may be, for example, 2-hydroxy-2-methylpropiophenone (HMPP), 1-hydroxy-cyclohexylphenyl-ketone, benzophenone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, oxy-phenylacetic acid 2-[2-iodo-2-phenyl-acetoxy-ethoxy]-ethyl ester, oxy-phenyl-acetic acid 2-[2-hydroxyethoxy]-ethyl ester, alpha-dimethoxy-alpha-phenylacetophenone, 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl ]-1-butanone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(eta5-2,4-cyclopentadiene-1-yl), bis[2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl]titanium, 4-isobutylphenyl-4'-methylphenyliodonium, hexafluorophosphate, and methylbenzoylformate.

[0142] Representative examples of the thermal polymerization initiator include at least one compound selected from the group consisting of benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, t-butyl peroxy-2-ethyl-hexanoate, cumyl hydroperoxide, and hydrogen peroxide, 2,2'-azobis(2-cyanobutane), 2,2'-azobis(methylbutyronitrile), 2,2'-azobis(isobutyronitrile) (AIBN), and 2,2'-azobisdimethyl-valeronitrile (AMVN).

[0143] The polymerization initiator can be decomposed by heat at 30°C to 100°C in the secondary battery or by light such as UV at room temperature (5°C to 30°C) to form radicals, and cross-linking bonds can be formed by free radical polymerization to polymerize the oligomer.

[0144] The curing may be carried out at a temperature of 50° C. to 100° C. for 0.5 to 48 hours, and preferably at a temperature of 60° C. to 80° C. for 0.5 to 24 hours.

[0145] Meanwhile, the curing may be performed in a sealed state of the battery case 300. For example, the battery case 300 containing the electrode assembly 100, the first electrolyte composition 210, and the second electrolyte composition 220 may be sealed with a cover 310 or the like, and then the second electrolyte composition 220 may be thermally cured by performing a heat treatment.

[0146] After the step (S4), the first electrolyte composition 210 is disposed inside the electrode assembly 100, and the second electrolyte composition 220 is cured to form a gel polymer electrolyte 220a, which may be disposed outside the electrode assembly 100. The first electrolyte composition impregnates the inside of the electrode assembly to reduce the resistance of the secondary battery, and the second electrolyte composition forms a gel polymer electrolyte outside the electrode assembly to improve cell rigidity and prevent electrolyte leakage. In addition, the first electrolyte composition 210 contains lithium bis(fluorosulfonyl)imide, but the second electrolyte composition 220 does not contain lithium bis(fluorosulfonyl)imide, so that the resistance of the secondary battery can be reduced, thermal stability can be improved, and corrosion of the electrode tab can be effectively prevented.

[0147] After the step (S4), a step of cooling the hardened second electrolyte composition may be further performed. For example, the cooling may be performed by leaving the hardened second electrolyte composition at room temperature.

[0148] After step (S4), the battery case 300 may be sealed to create a vacuum atmosphere inside the battery case 300. By forming the vacuum atmosphere, degassing of gases generated during curing may be performed.

[0149] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a block diagram of a semiconductor device according to an embodiment of the present invention;

[0150] Examples and Comparative Examples Experimental Example A: Use of a first electrolyte composition (liquid electrolyte composition) and a second electrolyte composition (gel polymer electrolyte composition) Example 1A 1. Manufacturing of separators Inorganic particles are Al2O3 (average particle size (D50 A ceramic coating layer-forming composition was prepared by adding 100% cellulose acetate (0.5 μm) and an acrylic binder to a solvent, water, in a weight ratio of 96:4. As the acrylic binder, a mixture of TRD 202A manufactured by JSR and AP-0821 manufactured by APEC was used.

[0151] The composition for forming a ceramic coating layer was applied by gravure coating to both sides of a polyethylene porous substrate (thickness: 9 μm, average pore size: 0.05 μm, porosity: 45% by volume) and dried to form a ceramic coating layer (thickness of one layer: 1.5 μm), thereby producing a separator (thickness: 12 μm = 1.5 μm + 9 μm + 1.5 μm).

[0152] 2. Manufacturing the electrode assembly The separator reel on which the separator was wound was unwound, and the separator was placed on a table. An adhesive was applied onto the separator in a pattern of a plurality of dots spaced apart from each other using a first nozzle. The adhesive application area (5.8875 mm 2 ) is the surface area where the separator and the positive electrode come into contact (24,889 mm 2 ) was 0.002366%. The adhesive was an acrylate-based adhesive, which is a copolymer containing repeating units derived from methyl methacrylate (MMA), 2-ethylhexyl acrylate (2-EHA) and 2-hydroxyethyl acrylate (2-HEA) in a weight ratio of 40:30:30. Next, the positive electrode sheet was unwound from the first electrode reel on which it was wound, and then cut with a first cutter to produce a positive electrode, which was then transported by a first transport device and adsorbed onto a first header. The first header was moved to the table side to attach the positive electrode onto the separator.

[0153] The table was then moved to the side and the separator was folded to one side to cover the positive electrode.

[0154] Next, the same adhesive as that used above was applied to the surface of the separator (the surface opposite to the surface where the separator and the positive electrode are in contact) in a pattern of multiple dots spaced apart from each other using a second nozzle.

[0155] Next, the negative electrode sheet was unwound from the second electrode reel and cut with a second cutter to produce a negative electrode, and the negative electrode was transported by a second transport device and attached to a second header. The second header was moved to the table side, and the negative electrode was attached to the surface of the separator (the surface opposite to the surface where the separator and the positive electrode contact each other).

[0156] Next, the table was moved laterally again, and the separator was folded to the other side to cover the negative electrode.

[0157] The above process was repeated several times to manufacture an electrode assembly in which 18 basic units each having a separator / positive electrode / separator / negative electrode stacked in sequence were stacked, in which the separator was folded in a zigzag shape.

[0158] Here, an aluminum electrode tab (positive electrode tab) was connected to the positive electrode, and a nickel electrode tab (negative electrode tab) was connected to the negative electrode.

[0159] Here, in the case of the positive electrode, the positive electrode active material is Li[Ni 0.8 Co 0.1 Mn 0.1 A positive electrode slurry was prepared by adding 1,2-dichlorophenyl ether (1,2-dichlorophenyl ether) and 1,2-dichlorophenyl ether (1,2-dichlorophenyl ether) as a binder and carbon black as a conductive material in a weight ratio of 97.5:1.5:1.0 to a solvent, N-methylpyrrolidone (NMP), and the positive electrode slurry was applied to both sides of an aluminum current collector as a positive electrode current collector, which was then dried and rolled to form a positive electrode active material layer.

[0160] In addition, in the case of the negative electrode, graphite as a negative electrode active material, styrene-butadiene rubber as a binder, carbon black as a conductive material, and carboxymethyl cellulose (CMC) as a thickener were added to water as a solvent in a weight ratio of 95.5:2.5:1.0:1.0 to prepare a negative electrode slurry, and the negative electrode slurry was applied to both sides of a copper current collector as a negative electrode current collector, which was then dried and rolled to form a negative electrode active material layer.

[0161] 3. Preparation of Electrolyte Composition (1) Preparation of the first electrolyte composition Lithium bis(fluorosulfonyl)imide (LiFSI) as the 1-1 lithium salt and LiPF6 as the 1-2 lithium salt were added to a solvent (a mixture of ethyl carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7) to give molar concentrations of 0.7 M and 0.3 M, respectively, to prepare a first electrolyte composition.

[0162] (2) Preparation of the second electrolyte composition LiPF6 as a second lithium salt was added to the second electrolyte composition to give a molar concentration of 1.0M relative to the second electrolyte composition, trimethylolpropane triacrylate as an oligomer was added to a solvent (a mixture of ethyl carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7) to give 5% by weight of the second electrolyte composition, and AIBN (Azobisisobutyronitrile) was added as a polymerization initiator to give 0.02% by weight relative to the weight of the second electrolyte composition to prepare a second electrolyte composition.

[0163] 4. Secondary battery manufacturing A pouch-type battery case made of aluminum was prepared as the battery case, and the electrode assembly was housed in the housing space of the battery case, where the positive electrode tab and the negative electrode tab were connected to the electrode assembly and arranged to protrude outside the electrode assembly.

[0164] Next, the amount of the first electrolyte composition was calculated and adjusted so that only the electrode assembly was impregnated, and the first electrolyte composition was injected into the battery case to impregnate the electrode assembly. After injecting the first electrolyte composition, the battery case was vacuum sealed and the inside of the electrode assembly was impregnated at room temperature for 60 hours.

[0165] Next, the second electrolyte composition was injected so as to be disposed outside the electrode assembly After the injection of the second electrolyte composition, the battery case was vacuum sealed.

[0166] Next, the second electrolyte composition injected into the battery case was cured to form a gel polymer electrolyte by heat treatment at a temperature of 65° C. for 5 hours.

[0167] The battery case was then cooled, sealed and degassed to prepare a secondary battery.

[0168] Meanwhile, the adhesive present in the electrode assembly was dissolved and removed by the solvent of the first electrolyte composition due to the injection of the first electrolyte composition, and as described below, traces of the adhesive application remained on the separator and electrodes after the adhesive was removed.

[0169] Example 2A A first electrolyte composition was prepared in the same manner as in Example 1A, except that the 1-1 lithium salt and the 1-2 lithium salt were added to the solvent to have molar concentrations of 0.7 M and 0.7 M, respectively.

[0170] A secondary battery was manufactured in the same manner as in Example 1A, except that the first electrolyte composition prepared above was used.

[0171] Example 3A A first electrolyte composition was prepared in the same manner as in Example 1A, except that the 1-1 lithium salt and the 1-2 lithium salt were added to the solvent to have molar concentrations of 0.6 M and 0.2 M, respectively.

[0172] A secondary battery was manufactured in the same manner as in Example 1A, except that the first electrolyte composition prepared above was used and no additional lithium salt addition step was performed.

[0173] Example 4A A secondary battery was produced in the same manner as in Example 1A, except that the second lithium salt was not added to the second electrolyte composition.

[0174] Example 5A A secondary battery was produced in the same manner as in Example 2A, except that the second lithium salt was not added to the second electrolyte composition.

[0175] Comparative Example 1A 1. Preparation of electrolyte composition An electrolyte composition was prepared in the same manner as the first electrolyte composition of Example 1A, except that the 1-1 lithium salt was not used and the 1-2 lithium salt (LiPF6) was added to the solvent to a molar concentration of 1.0 M.

[0176] 2. Manufacturing of secondary batteries A pouch-type battery case made of aluminum was prepared as the battery case, and the electrode assembly was housed in the storage space of the battery case. Here, the positive electrode tab and the negative electrode tab were connected to the electrode assembly and arranged to protrude outside the electrode assembly. The battery case, electrode assembly, positive electrode tab, and negative electrode tab used above were the same as those used in Example 1A.

[0177] Next, the electrolyte composition prepared above was injected into the inner space of the battery case, vacuum sealed, and allowed to impregnate the inside of the electrode assembly at room temperature for 60 hours.

[0178] The battery case was then cooled, sealed and degassed to prepare a secondary battery.

[0179] The secondary battery prepared in the above-mentioned manner is different from Example 1A in that two different electrolyte compositions were not used, but one electrolyte composition was injected into the battery case in one step, and that a gel polymer electrolyte was not used, but only a liquid electrolyte was used.

[0180] Comparative example 2A 1. Preparation of electrolyte composition An electrolyte composition was prepared in the same manner as the first electrolyte composition of Example 1A, except that the 1-2 lithium salt was not used and the 1-1 lithium salt (LiFSI) was added to the solvent to a molar concentration of 1.0 M.

[0181] 2. Manufacturing of secondary batteries A pouch-type battery case made of aluminum was prepared as the battery case, and the electrode assembly was housed in the housing space of the battery case.

[0182] Next, the electrolyte composition prepared above was injected into the inner space of the battery case, vacuum sealed, and allowed to impregnate the inside of the electrode assembly at room temperature for 60 hours.

[0183] The battery case was then cooled, sealed and degassed to prepare a secondary battery.

[0184] The secondary battery prepared in the above-mentioned manner is different from Example 1A in that two different electrolyte compositions were not used, but one electrolyte composition was injected into the battery case in one step, and that a gel polymer electrolyte was not used, but only a liquid electrolyte was used.

[0185] Comparative example 3A 1. Preparation of electrolyte composition An electrolyte composition was prepared in the same manner as the first electrolyte composition of Example 1A, except that the 1-1 lithium salt and the 1-2 lithium salt were added to the solvent to have molar concentrations of 0.3 M and 0.7 M, respectively.

[0186] 2. Manufacturing of secondary batteries A pouch-type battery case made of aluminum was prepared as the battery case, and the electrode assembly was housed in the housing space of the battery case.

[0187] Next, the electrolyte composition prepared above was injected into the inner space of the battery case, vacuum sealed, and allowed to impregnate the inside of the electrode assembly at room temperature for 60 hours.

[0188] The battery case was then cooled, sealed and degassed to prepare a secondary battery.

[0189] The secondary battery prepared in the above-mentioned manner is different from Example 1A in that two different electrolyte compositions were not used, but one electrolyte composition was injected into the battery case in one step, and that a gel polymer electrolyte was not used, but only a liquid electrolyte was used.

[0190] Experimental Example 1A. Observation of adhesive marks on the separator surface The separator corresponding to the surface where the electrode and the separator were in contact in the secondary battery of Example 1A was cut and the surface was observed. A photograph of the surface of the separator separated from the secondary battery of Example 1A is shown in FIG.

[0191] As shown in FIG. 15, traces of adhesive application were observed in the photograph of the surface of the separator of Example 1A.

[0192] Experimental Example 2A. Resistance Evaluation In the secondary batteries of Examples 1A to 5A and Comparative Examples 1A to 3A, the resistance value was calculated using the voltage change (ΔV) measured when discharging at a 2.5C rate for 10 seconds at SOC 50%.

[0193] When the resistance value of the secondary battery of Comparative Example 1A was taken as 100%, the relative ratios of the resistance values ​​of the secondary batteries of Examples 1A to 5A and Comparative Examples 1A to 3A are shown in Table 1 below.

[0194] Experimental Example 3A. Observation of Tab Corrosion The secondary batteries manufactured in Examples 1A to 5A and Comparative Examples 1A to 3A were fully charged and then stored at 60° C. for two weeks, after which the positive electrode tab was visually inspected for corrosion. Five secondary batteries each in Examples 1A to 5A and Comparative Examples 1A to 3A were prepared, and the above experiment was performed five times.

[0195] If no corrosion occurred on the positive electrode tab, it was rated as "Pass," and if corrosion occurred, it was rated as "Fail." The number of times that the test was rated as "Pass" out of the total number of tests (5 tests) is shown in Table 1.

[0196] Experimental Example 4A. Measurement of leakage volume The amount of electrolyte leakage was measured for Examples 1A to 5A and Comparative Examples 1A to 3A. A 5 cm cut was made on the side of each secondary battery, and the amount of electrolyte leakage was measured after leaving the battery for 3 days with the cut part at the bottom. The results are shown in Table 1 below.

[0197] [Table 1]

[0198] Referring to Table 1, the secondary batteries of Examples 1A to 5A had reduced resistance, no tab corrosion was observed, and electrolyte leakage was hardly observed.

[0199] However, in the case of Comparative Example 1A, since lithium bis(fluorosulfonyl)imide was not used, corrosion of the electrode tab did not occur, but the resistance increased significantly and the gel polymer electrolyte was not positioned outside the electrode assembly, resulting in a considerable amount of electrolyte leakage outside the secondary battery.

[0200] In addition, in Comparative Examples 2A and 3A, lithium bis(fluorosulfonyl)imide was disposed outside the electrode assembly and came into contact with the electrode tabs, which was undesirable as corrosion of the electrode tabs was observed, and a significant amount of electrolyte leakage occurred outside the secondary battery as the gel polymer electrolyte was not disposed outside the electrode assembly.

[0201] Experimental Example B: Use of the first electrolyte composition (gel polymer electrolyte composition) and the second electrolyte composition (gel polymer electrolyte composition) Example 1B 1. Manufacturing of separators Inorganic particles are Al2O3 (average particle size (D 50 A ceramic coating layer-forming composition was prepared by adding 100% cellulose acetate (0.5 μm) and an acrylic binder to a solvent, water, in a weight ratio of 96:4. A mixture of TRD 202A manufactured by JSR and AP-0821 manufactured by APEC was used as the acrylic binder.

[0202] The composition for forming a ceramic coating layer was applied by gravure coating to both sides of a polyethylene porous substrate (thickness: 9 μm, average pore size: 0.05 μm, porosity: 45% by volume), and then dried to form a ceramic coating layer (thickness of one layer: 1.5 μm), thereby producing a separator (thickness: 12 μm = 1.5 μm + 9 μm + 1.5 μm).

[0203] 2. Manufacturing the electrode assembly The separator reel on which the separator was wound was unwound, and the separator was placed on a table. An adhesive was applied onto the separator in a pattern of a plurality of dots spaced apart from each other using a first nozzle. The applied area of ​​the adhesive (5.8875 mm 2 ) is the surface area where the separator and the positive electrode come into contact (24,889 mm 2 ) was 0.002366%. The adhesive was an acrylate-based adhesive, which is a copolymer containing repeating units derived from methyl methacrylate (MMA), 2-ethylhexyl acrylate (2-EHA) and 2-hydroxyethyl acrylate (2-HEA) in a weight ratio of 40:30:30. Next, the positive electrode sheet was unwound from the first electrode reel on which it was wound, and then cut with a first cutter to produce a positive electrode, which was then transported by a first transport device and adsorbed onto a first header. The first header was moved to the table side to attach the positive electrode onto the separator.

[0204] The table was then moved to the side and the separator was folded to one side to cover the positive electrode.

[0205] Next, the same adhesive as that used above was applied to the surface of the separator (the surface opposite to the surface where the separator and the positive electrode are in contact) in a pattern of multiple dots spaced apart from each other using a second nozzle.

[0206] Next, the negative electrode sheet was unwound from the second electrode reel and cut with a second cutter to produce a negative electrode, and the negative electrode was transported by a second transport device and attached to a second header. The second header was moved to the table side, and the negative electrode was attached to the surface of the separator (the surface opposite to the surface where the separator and the positive electrode contact each other).

[0207] Next, the table was moved laterally again, and the separator was folded to the other side to cover the negative electrode.

[0208] The above process was repeated several times to manufacture an electrode assembly in which 18 basic units each having a separator / positive electrode / separator / negative electrode stacked in sequence were stacked, in which the separator was folded in a zigzag shape.

[0209] Here, an aluminum electrode tab (positive electrode tab) was connected to the positive electrode, and a nickel electrode tab (negative electrode tab) was connected to the negative electrode.

[0210] Here, in the case of the positive electrode, the positive electrode active material is Li[Ni 0.8 Co 0.1 Mn 0.1 A positive electrode slurry was prepared by adding 1,02-tetrafluoroethylene (1,3-dimethylphenyl)-2 ...

[0211] In addition, in the case of the negative electrode, graphite as a negative electrode active material, styrene-butadiene rubber as a binder, carbon black as a conductive material, and carboxymethyl cellulose (CMC) as a thickener were added to water as a solvent in a weight ratio of 95.5:2.5:1.0:1.0 to prepare a negative electrode slurry, and the negative electrode slurry was applied to both sides of a copper current collector as a negative electrode current collector, which was then dried and rolled to form a negative electrode active material layer.

[0212] 3. Preparation of Gel Polymer Electrolyte Composition (1) Preparation of the First Gel Polymer Electrolyte Composition Lithium bis(fluorosulfonyl)imide (LiFSI) as the 1-1 lithium salt and LiPF6 as the 1-2 lithium salt were added to a solvent (ethylene carbonate (EC) and ethyl methyl carbonate (EMC) mixed in a volume ratio of 3:7) to give molar concentrations of 0.9M and 0.3M, respectively. Trimethylolpropane triacrylate as an oligomer was added to the solvent to give 5% by weight based on the weight of the composition. Azobisisobutyronitrile (AIBN) as a polymerization initiator was added to the solvent to give 0.02% by weight based on the weight of the composition, to produce a first gel polymer electrolyte composition.

[0213] (2) Preparation of the Second Gel Polymer Electrolyte Composition A second gel polymer electrolyte composition was produced in the same manner as the first gel polymer electrolyte composition, except that the 1-1 lithium salt and the 1-2 lithium salt were not contained.

[0214] 4. Secondary battery manufacturing A pouch-type battery case made of aluminum was prepared as the battery case, and the electrode assembly was housed in the housing space of the battery case, where the positive electrode tab and the negative electrode tab were connected to the electrode assembly and arranged to protrude outside the electrode assembly.

[0215] Next, the amount of the first gel polymer electrolyte composition was calculated and adjusted so that only the electrode assembly was impregnated, and the first gel polymer electrolyte composition was injected into the battery case to impregnate the electrode assembly. After injecting the first gel polymer electrolyte composition, the battery case was vacuum sealed, and the inside of the electrode assembly was impregnated at room temperature for 60 hours.

[0216] Next, the second gel polymer electrolyte composition was injected so as to be disposed outside the electrode assembly, and after the injection of the second gel polymer electrolyte composition, the electrode assembly was vacuum sealed.

[0217] Next, the first gel polymer electrolyte composition and the second gel polymer electrolyte composition injected into the battery case were cured by heat treatment at a temperature of 65° C. for 5 hours.

[0218] The battery case was then cooled, sealed and degassed to produce a secondary battery.

[0219] Meanwhile, the adhesive present in the electrode assembly was dissolved and removed by the solvent of the first gel polymer electrolyte composition due to the injection of the first gel polymer electrolyte composition, and as described below, traces of the adhesive application remained on the separator and electrodes after the adhesive was removed.

[0220] Example 2B A first gel polymer electrolyte composition was prepared in the same manner as in Example 1B, except that the 1-1 lithium salt and the 1-2 lithium salt were added to the solvent to have molar concentrations of 0.8M and 0.4M, respectively.

[0221] A secondary battery was manufactured in the same manner as in Example 1B, except that the first gel polymer electrolyte composition prepared above was used.

[0222] Example 3B A first gel polymer electrolyte composition was prepared in the same manner as in Example 1B, except that the 1-1 lithium salt and the 1-2 lithium salt were added to the solvent to have molar concentrations of 0.7M and 0.5M, respectively.

[0223] A secondary battery was manufactured in the same manner as in Example 1B, except that the first gel polymer electrolyte composition prepared above was used.

[0224] Example 4B A first gel polymer electrolyte composition was prepared in the same manner as in Example 1B, except that the 1-1 lithium salt and the 1-2 lithium salt were added to the solvent to have molar concentrations of 0.6 M and 0.2 M, respectively.

[0225] A secondary battery was manufactured in the same manner as in Example 1B, except that the first gel polymer electrolyte composition prepared above was used.

[0226] Comparative example 1B 1. Manufacturing the electrode assembly An electrode assembly was prepared in the same manner as in Example 1B.

[0227] 2. Preparation of Gel Polymer Electrolyte Composition A gel polymer electrolyte composition was prepared in the same manner as the first gel polymer electrolyte composition of Example 1B, except that the first-1 lithium salt was not used and the first-2 lithium salt (LiPF6) was added to the solvent to a molar concentration of 1.0 M.

[0228] 3. Secondary battery manufacturing A pouch-type battery case made of aluminum was prepared as the battery case, and the electrode assembly was housed in the storage space of the battery case. Here, the positive electrode tab and the negative electrode tab were connected to the electrode assembly and arranged to protrude outside the electrode assembly. The battery case, electrode assembly, positive electrode tab, and negative electrode tab used above were the same as those used in Example 1B.

[0229] Next, the gel polymer electrolyte composition prepared above was injected into the inner space of the battery case, vacuum sealed, and allowed to impregnate the inside of the electrode assembly at room temperature for 60 hours.

[0230] Next, the gel polymer electrolyte composition injected into the battery case was cured by heat treatment at a temperature of 65° C. for 5 hours.

[0231] The battery case was then cooled, sealed and degassed to prepare a secondary battery.

[0232] The secondary battery prepared in the above-mentioned manner is different from that in Example 1B in that two different gel polymer electrolyte compositions are not used, but one gel polymer electrolyte composition is injected into the battery case in one step and cured.

[0233] Comparative Example 2B Instead of the second gel polymer electrolyte composition prepared in Example 1B, the same gel polymer electrolyte composition as the first gel polymer electrolyte composition prepared in Example 1B was prepared as a second gel polymer electrolyte composition.

[0234] A secondary battery was manufactured in the same manner as in Example 1B, except that the second gel polymer electrolyte composition prepared above was used.

[0235] Experimental Example Experimental Example 1B. Evaluation of Resistance For the secondary batteries of Examples 1B to 4B, Comparative Example 1B, and Comparative Example 2B, the resistance values ​​calculated using the voltage change (ΔV) measured when discharging at a 2.5C rate for 10 seconds at SOC 50% are shown in Table 2 below.

[0236] Experimental Example 2B. Evaluation of thermal stability The secondary batteries of Examples 1B to 4B and Comparative Examples 1B and 2B were fully charged to SOC 100%, then placed in a hot box and heated at a rate of 0.5°C / min. After the temperature in the hot box reached 150°C, the temperature was maintained for 2 hours to evaluate whether ignition occurred.

[0237] If no ignition occurred, the test was rated as "Pass," and if ignition occurred, the test was rated as "Fail." The results are shown in Table 2.

[0238] Experimental Example 3B. Observation of Tab Corrosion The secondary batteries manufactured in Examples 1B to 4B and Comparative Examples 1B and 2B were fully charged and then stored at 60° C. for two weeks, and then visually observed to see whether corrosion had occurred on the positive electrode tab.

[0239] If no corrosion occurred on the positive electrode tab, it was rated as "Pass," and if corrosion occurred, it was rated as "Fail." The results are shown in Table 2.

[0240] [Table 2]

[0241] Referring to Table 2, it can be seen that the secondary batteries of Examples 1B to 3B not only have reduced resistance and excellent thermal stability, but also no tab corrosion is observed.

[0242] On the other hand, Example 4B has a slightly increased resistance compared to Examples 1B to 3B, but is excellent in thermal stability and tab corrosion prevention.

[0243] However, in the case of Comparative Example 1B, since lithium bis(fluorosulfonyl)imide is not used, the thermal stability shows a very poor result.

[0244] In addition, in Comparative Example 2B, lithium bis(fluorosulfonyl)imide was disposed outside the electrode assembly and contacted the electrode tabs, which was undesirable because corrosion of the electrode tabs was observed. [Explanation of symbols]

[0245] 100 electrode assembly U base unit 110 1st electrode 110a One end of the first electrode 120 2nd electrode 120a: One end of the second electrode 130 Separator 131 Porous substrate 132a, 132b Ceramic coating layer 140 Applied adhesive 210 First electrolyte composition 220 Second electrolyte composition 220a Gel polymer electrolyte 300 Battery Case 310 Cup section 320 Cover 400, 500 electrode tab 610 First electrode reel 620 Second electrode reel 630 Separator reel 700 Tables 810 First Cutter 820 No. 2 Cutter 910 1st transfer device 920 Second transfer device 1010 First Header 1020 2nd Header 1101 First electrode sheet 1201 Second electrode sheet 1110 No. 1 nozzle 1120 No. 2 nozzle

Claims

1. (S1) housing an electrode assembly in a battery case; (S2) injecting a first electrolyte composition into the battery case to impregnate the electrode assembly; (S3) injecting a second electrolyte composition into the battery case; (S4) curing the second electrolyte composition; an electrode tab is connected to the electrode assembly, and the electrode tab is extended to the outside of the electrode assembly; The first electrolyte composition includes a first-1 lithium salt including at least one selected from the group consisting of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and a first solvent; the second electrolyte composition includes an oligomer and a second solvent; The second electrolyte composition does not contain lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

2. The method for producing a secondary battery according to claim 1 , wherein the first electrolyte composition is a liquid electrolyte composition.

3. the first electrolyte composition is a gel polymer electrolyte composition; The method for manufacturing a secondary battery according to claim 1 , wherein the first electrolyte composition further comprises an oligomer.

4. The method for producing a secondary battery according to claim 3 , wherein in the step (S4), the first electrolyte composition and the second electrolyte composition are both cured.

5. The method for producing a secondary battery according to claim 3 , further comprising, after the step (S2), a step of curing the first electrolyte composition.

6. The first electrolyte composition is lithium hexafluorophosphate (LiPF 6 ), lithium perchlorate (LiClO 4 ), lithium hexafluoroarsenate (LiAsF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium hexafluoroantimonate (LiSbF 6 ), lithium tetraoxoaluminate (LiAlO 4 ), lithium tetrachloroaluminate (LiAlCl 4 ), lithium trifluoromethanesulfonate (LiCF 3 SO 3 ), lithium nonafluorobutanesulfonate (LiC 4 F 9 SO 3 ), lithium chloride (LiCl), lithium iodide (LiI), lithium bis(oxalato)borate (LiB(C 2 O 4 ) 2 ), lithium bis(pentafluoroethanesulfonyl)imide (LiN(C 2 F 5 SO 2 ) 2 2. The method for producing a secondary battery according to claim 1, further comprising a first-second lithium salt comprising at least one selected from the group consisting of lithium fluoroalkylborate (LiFAB) and lithium 2-trifluoromethyl-4,5-dicyanoimidazole (LiTDI).

7. the second electrolyte composition further comprises a second lithium salt; The second lithium salt is lithium hexafluorophosphate (LiPF 6 ), lithium perchlorate (LiClO 4 ), lithium hexafluoroarsenate (LiAsF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium hexafluoroantimonate (LiSbF 6 ), lithium tetraoxoaluminate (LiAlO 4 ), lithium tetrachloroaluminate (LiAlCl 4 ), lithium trifluoromethanesulfonate (LiCF 3 SO 3 ), lithium nonafluorobutanesulfonate (LiC 4 F 9 SO 3 ), lithium chloride (LiCl), lithium iodide (LiI), lithium bis(oxalato)borate (LiB(C 2 O 4 ) 2 ), lithium bis(pentafluoroethanesulfonyl)imide (LiN(C 2 F 5 SO 2 ) 2 2. The method for producing a secondary battery according to claim 1, wherein the lithium fluoride-containing compound is at least one selected from the group consisting of lithium fluoroalkylborate (LiFAB) and lithium 2-trifluoromethyl-4,5-dicyanoimidazole (LiTDI).

8. 2. The method for producing a secondary battery according to claim 1, wherein the oligomer includes at least one selected from the group consisting of a fluorine-based oligomer, a polycarbonate-based oligomer, and a polysiloxane-based oligomer.

9. The method for producing a secondary battery according to claim 1 , wherein the second electrolyte composition further comprises a polymerization initiator.

10. The method for manufacturing a secondary battery according to claim 1 , wherein the electrode tab comprises aluminum.

11. The method of claim 1 , wherein the first electrolyte composition is injected so as not to contact the electrode tabs.

12. The method of claim 1 , wherein in step (S3), the second electrolyte composition is injected outside the electrode assembly.

13. After the step (S4), the first electrolyte composition is disposed inside the electrode assembly, The method of claim 1 , wherein the second electrolyte composition is cured to form a gel polymer electrolyte, and the gel polymer electrolyte is disposed outside the electrode assembly.

14. 2. The method of claim 1, wherein the electrode assembly is formed by stacking electrodes and separators alternately, and an adhesive is applied to a surface of at least one of the electrodes and the separators to adhere the electrodes and the separators to each other.

15. The separator includes a porous substrate and a ceramic coating layer disposed on both sides of the porous substrate; The method for manufacturing a secondary battery according to claim 14 , wherein the ceramic coating layer comprises 92% by weight or more and less than 100% by weight of inorganic particles and more than 0% by weight and 8% by weight or less of a binder.

16. The method of claim 14 , wherein the adhesive is applied in a plurality of patterns spaced apart from each other.

17. The method for producing a secondary battery according to claim 14 , wherein the adhesive is dissolved in the first electrolyte composition by injecting the first electrolyte composition.

18. The method for manufacturing a secondary battery according to claim 17 , wherein after the adhesive is dissolved, a trace of adhesive remains on a surface of one of the separator and the electrode.

19. the electrodes include a first electrode and a second electrode; The method of claim 14, wherein the electrode assembly is manufactured by a method including the steps of: (a) forming a first electrode assembly by bonding a first electrode to a second electrode assembly; (a) applying the adhesive to at least a portion of the separator and the first electrode; (b) adhering the separator and the first electrode with the applied adhesive; (c) folding one side of the separator to cover the first electrode; (d) applying the adhesive to at least a portion of the separator and the second electrode; (e) adhering the separator and the second electrode with the applied adhesive; (d) folding the other side of the separator to cover the second electrode.

Citation Information

Patent Citations

  • Lithium-ion secondary battery

    JP2000133220A

  • Electrolyte and battery using the same

    JP2004247062A

  • Nonaqueous electrolyte secondary battery and its manufacturing method

    JP2007207450A

  • Electrolyte layer for lithium ion secondary battery

    JP2007257863A

  • Method for manufacturing lithium ion secondary battery

    JP2017050215A